2019
DOI: 10.1039/c8an02218f
|View full text |Cite
|
Sign up to set email alerts
|

Towards identifying the mode of action of drugs using live-cell FTIR spectroscopy

Abstract: Fourier transform infrared spectroscopy (FTIR) has been shown to be a promising tool for identifying the mode of action of drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…A significant decrease was observed, in the bands related to the stretching of O-P-O and C-O at 1080 cm −1 and 1050 cm −1 , respectively. Those spectral changes are related to changes in the DNA-phosphate backbone, because of the DNA disintegrating effect of doxorubicin [121].…”
Section: Dna Damage At the Cellular Levelmentioning
confidence: 99%
“…A significant decrease was observed, in the bands related to the stretching of O-P-O and C-O at 1080 cm −1 and 1050 cm −1 , respectively. Those spectral changes are related to changes in the DNA-phosphate backbone, because of the DNA disintegrating effect of doxorubicin [121].…”
Section: Dna Damage At the Cellular Levelmentioning
confidence: 99%
“…We have recently shown that ATR FTIR spectroscopy combined with principal component analysis (PCA) is a powerful technique to distinguish the response of MDA-MB-231 cells, a triple negative cell, based on their different modes of actions. The results have shown that drugs with the same mode of action (tamoxifen and toremifene) were clustered together and well-separated from other drugs of different modes of action (imatinib and doxorubicin) …”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the band at 1087 cm −1 was used instead to map the nucleus of cells based on the ν sym (PO 2 ) – in the DNA backbone because it is a stronger band. However, using the band at 1714 cm −1 to map the distribution of the DNA is more specific than the 1087 cm −1 band as other non-nucleus specific biocomponents such as RNA, phospholipid, phosphorylated protein, 35 and other phosphate containing metabolites such as adenosine triphosphate and adenosine diphosphate can contribute to the absorbance in that region. As a result, images generated from the integrated absorbance within the 1102–1065 cm −1 spectral range (Figs.…”
Section: Resultsmentioning
confidence: 99%